Knowledge sharing practices in construction organisation in Nigeria - Mohammed Alhaji, Kasimu (2013)
Knowledge has not been properly shared in the Construction organisations during the construction process, thereby affected the performance of the construction organisational outputs in terms of quality, time and cost. The aim of the paper is to investigate the mode of practicing knowledge sharing in the construction organisations. The research methodology adopted for this research work is a mixed method research approach. A total of three hundred and fifty (350) questionnaires were distributed to Architect, Quantity Surveying, Engineers, Builders and other professionals across the selected construction organisations. The method of analysis employed is descriptive,because descriptive is a transformation of raw data in a form that make them easy to understand. The results show that face to face interaction, site meeting, internal training, project briefing means of sharing knowledge, best practice and experiences of experts and engineers in the construction organisations. Therefore, the paper recommended that, the head of construction organisations should encourage engineers and experts to share knowledge and experiences to improvethe quality of project delivery, working morale and innovation in the construction organisations.